2013
DOI: 10.1016/j.bbmt.2012.08.015
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Trial of One versus Two Doses of Influenza Vaccine after Allogeneic Transplantation

Abstract: Influenza infection following allogeneic hematopoietic cell transplantation (allo-HCT) can result in severe complications. The effectiveness of the annual vaccine depends on age, immune competence and the antigenic potential of the 3 strains included (1). . We hypothesized that a second vaccine dose, the standard of care for vaccine-naïve children, might improve post-HCT immune responses. Patients >60 days post-HCT were randomized to receive either 1 (n=33) or 2 (n=32) influenza vaccine doses separated by one … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
64
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(70 citation statements)
references
References 30 publications
5
64
1
Order By: Relevance
“…One study has not demonstrated further benefit from 2 doses in pediatric BMT recipients who have not received influenza vaccine posttransplant, and therefore, just 1 dose is given annually thereafter. 15 For healthy family members aged 2 to 8 years, live attenuated influenza vaccine (FluMist, MedImmune) or the inactivated flu shot is considered equally effective. LAIV has limited ability to spread from person to person, but in general, patients who require protective isolation or are hospitalized should not be exposed to LAIV.…”
Section: Influenza Vaccinementioning
confidence: 99%
“…One study has not demonstrated further benefit from 2 doses in pediatric BMT recipients who have not received influenza vaccine posttransplant, and therefore, just 1 dose is given annually thereafter. 15 For healthy family members aged 2 to 8 years, live attenuated influenza vaccine (FluMist, MedImmune) or the inactivated flu shot is considered equally effective. LAIV has limited ability to spread from person to person, but in general, patients who require protective isolation or are hospitalized should not be exposed to LAIV.…”
Section: Influenza Vaccinementioning
confidence: 99%
“…[1][2][3] Those who have undergone allogeneic SCT are at even higher risk. 4,5 Furthermore, influenza in these children may cause delay in planned anticancer therapy and can a Division of Oncology, and Dr Freedman conceptualized and designed the study, performed the data analysis and interpretation of the data, and drafted and revised the manuscript; Dr Reilly conceptualized and designed the study, participated in analysis and interpretation of the data, and critically reviewed and revised the manuscript; Mrs Powell conceptualized and designed the study, drafted key parts of the manuscript, was critical in implementing our process changes in the clinical setting, and critically reviewed and revised the manuscript; Dr Bailey conceptualized and designed the study, was critical in implementing the electronic medical record aspects of our study, participated in analysis and interpretation of the data, drafted key parts of the manuscript, and critically reviewed and revised the manuscript; and all authors approved the final manuscript as submitted. Accepted for publication Sep 8, 2014 contribute to poorer overall and event-free survival.…”
mentioning
confidence: 99%
“…8,9 In transplant patients, a recent study in adults found no difference in increased T-cell-mediated immunity in patients given 1 versus 2 doses of the vaccine posttransplantation, arguing that attention to providing $1 dose of the immunization in patients with cancer can produce significant benefit. 5 Conversely, 2 recent pediatric studies demonstrated better immunogenicity in children with cancer after repeated doses and with use of higher adult doses. 10,11 Although the response to vaccination may be suboptimal and the influenza vaccine imperfect, studies to date do demonstrate seroconversion and protection for children with cancer.…”
mentioning
confidence: 99%
“…Data regarding the utility of 1‐ vs 2‐dose influenza vaccine regimens post‐HSCT are conflicting. In general, studies using nonadjuvanted vaccine demonstrate no benefit of a second dose whereas studies using ASO3‐adjuvanted 2009 H1N1 pandemic vaccine demonstrate additional benefit from a second vaccine administration. Most recently, Karras et al.…”
Section: Influenzamentioning
confidence: 99%
“…Most recently, Karras et al. addressed the 1‐ vs 2‐dose question in a study of adult and pediatric allogeneic HSCT recipients beyond 60 days posttransplant who were randomized to 1 versus 2 doses of nonadjuvanted, seasonal TIV during the 2010‐2011 influenza season . No significant differences in frequency of seroprotection or seroconversion were found.…”
Section: Influenzamentioning
confidence: 99%